2013
DOI: 10.1002/ejic.201300008
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Centimeter‐Sized Ba2LaFeNb4O15 Crystals from High‐Temperature Solution under a Controlled Atmosphere

Abstract: Centimeter-sized single crystals of Ba 2 LaFeNb 4 O 15 were grown from a high-temperature solution by using LiBO 2 flux and a sealed platinum assembly. The obtained single crystals display the same physical properties as their ceramic counterparts. A frequency-dependent dielectric permittivity maximum was found (T m = 100 K at 5 kHz), which indicates relaxor behavior. Magnetic susceptibility measurements revealed purely paramagnetic behavior between 10 and 350 K. X-ray diffraction measurements of Ba 2 LaFeNb 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…Here, an excess of NaF was added in order to obtain a 75 %mol of Na 3 V 2 (PO 4 ) 2 F 3 and 25 %mol of NaF mixture for the pellet which was sintered at 800 °C during 1 hour under 95%/5% Ar/H 2 . This sintered pellet was placed into a platinum assembly sealed under primary vacuum 22 . The platinum assembly was first heated for 24 h at 1050 °C in a vertical resistive furnace, then cooled down to 950 °C at 0.5 °C.h -1 within a longitudinal thermal gradient about 0.5 °C.cm -1 and finally cooled down to room temperature at 120 °C.h -1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, an excess of NaF was added in order to obtain a 75 %mol of Na 3 V 2 (PO 4 ) 2 F 3 and 25 %mol of NaF mixture for the pellet which was sintered at 800 °C during 1 hour under 95%/5% Ar/H 2 . This sintered pellet was placed into a platinum assembly sealed under primary vacuum 22 . The platinum assembly was first heated for 24 h at 1050 °C in a vertical resistive furnace, then cooled down to 950 °C at 0.5 °C.h -1 within a longitudinal thermal gradient about 0.5 °C.cm -1 and finally cooled down to room temperature at 120 °C.h -1 .…”
Section: Methodsmentioning
confidence: 99%
“…This sintered pellet was placed into a platinum assembly sealed under primary vacuum. 22 The platinum assembly was first heated for 24 h at 1050 °C in a vertical resistive furnace, then cooled down to 950 °C at 0.5 °C• h −1 within a longitudinal thermal gradient about 0.5 °C•cm −1 , and finally cooled down to room temperature at 120 °C•h −1 . The as-grown piece was cut into a single crystal (2.4 × 3.1 × 1.4 mm 3 ) oriented along 3 crystallographic directions [100], [010], and [001] checked by Laue X-rays backscattering.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The incorporation of Fe ion in the B sites for electroneutrality seems not trigger an anticipatory multiferroic property in Ba 2 REFeNb 4 O 15 since the parasitic phase BaFe 12 O 19 is responsible for the magnetic properties. [12][13][14] But it could restrain the cooperative displacements as well as the polar domain formation, which has signicant inuence on their dielectric behavior, for example, in Ba 2 LaFeNb 4 O 15 ceramics with smaller permittivity compared with Ba 2 LaTi 2 Nb 3 O 15 . 15 Unfortunately, the detailed charge transport mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 Similarly, O. Raymond and his co-workers investigated the ferroelectromagnetic Pb(Fe 0.5 Nb 0.5 )O 3 ceramics, and concluded that the presence of Fe 2+ fundamentally contributes to the nonlocalized conduction and the oxygen vacancies are responsible for the dielectric relaxation process. 19 Actually, signicant dielectric losses can be observed when Fe ions are introduced in the TTB compounds at room temperature (RT), 12,20,21 which may be associated with nonlocalized conduction. For a better understanding of the physical nature of the electrical properties and relaxation processes for Fe-containing TTBs, we designed and synthesized a new compound, Ba 2 CeFeNb 4 O 15 (BCFN).…”
Section: Introductionmentioning
confidence: 99%
“…an attempt to increase the crystal size by avoiding the flux creeping and its volatilization from the solution, a crystal growth was performed with BaZrO 3 -BBO 35:65 molar ratio under controlled atmosphere in a sealed and gas-proof platinum assembly for saturating the vapor pressure as previously reported by Albino et al[66]. The same thermal protocol was performed as above-mentioned.…”
mentioning
confidence: 99%